2018
DOI: 10.1007/s11695-018-3119-x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes of Laparoscopic and Robotic Revisional Bariatric Surgery in a Complex Patient Population

Abstract: RRBS is associated with a shorter length of stay than LRBS in complex procedures and has at least an equivalent safety profile. Long-term follow-up data is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Severe early complications after primary laparoscopic RYGB are relatively uncommon nowadays, with anastomotic leak rates ranging between 0.1 and 1.2% [8][9][10][11]. Higher morbidity and mortality have however been described after laparoscopic revisional RYGB, with anastomotic leak rates ranging from 4.5 to 11.8% [11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…Severe early complications after primary laparoscopic RYGB are relatively uncommon nowadays, with anastomotic leak rates ranging between 0.1 and 1.2% [8][9][10][11]. Higher morbidity and mortality have however been described after laparoscopic revisional RYGB, with anastomotic leak rates ranging from 4.5 to 11.8% [11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…Regarding the LOS, results to date are contradictory. A reduction in the LOS was found in one study using the robot [27], while the registry data showed an extended LOS [28]. In the study by Clapp et al [28], the clear differences between cohorts regarding index operation and procedure must be mentioned.…”
Section: Prosmentioning
confidence: 94%
“…However, there was a significantly higher proportion of technical simple gastric band removals in the laparoscopic revision group, while consecutively the relative share of complex RYGB operations was higher in the robot group. One study reported a significant reduction in operative time in a subgroup of rRRYGB (193 min, da Vinci Xi) versus rLRYGB (238 min) [27]. We also used the Xi System.…”
Section: Prosmentioning
confidence: 99%
See 2 more Smart Citations